Embodiments of Evil: Gog and Magog - Seyed-Gohrab, A.A (Iranian Studies Series, 2011)
Gog and Magog, as archetypes of evil, have dwelt in our consciousness since their threatening appearance in the Bible and Quran. Maps, literature and texts ranging from Medieval Europe, the Byzantine and Arab world, in Berber, Persian and Indonesian traditions, to contemporary internet texts: all use these imaginary monstrous creatures. The figures are constantly reinterpreted as the enemies of order change. This volume reveals in eight essays the images of the 'Other' in genres ranging from contemporary folk religion on the internet to the rich literary heritage of Alexander romances.